Students’ Motivation In English Learning During the Pandemic: A Study of Year Eight Students at SMP Negeri 27 Makassar - Adhe Ramdhany Syam; Chairil Anwar Korompot; Maemuna Muhayyang (PERFORMANCE: JOURNAL OF ENGLISH EDUCATION AND LITERATURE, 2023)
This study aims to determine the motivation of students in learning English during the Covid-19 pandemic, with a specific focus on eighth-grade students at SMP Negeri 27 Makassar. And to explores the intrinsic and extrinsic factors that drive students’ motivation in English learning. The study utilized questionnaires and interviews as research instruments to collect data on student motivation levels. Data analysis was conducted using a 4-point Likert scale to determine the levels of intrinsic and extrinsic motivation. The findings of the study indicate that students at SMP Negeri 27 Makassar exhibited a remarkably high level of intrinsic motivation, driven by students' aspirations to enhance their understanding and proficiency in the English language. Additionally, the influence of extrinsic motivation factors showed a high level, attributed to the presence of a conducive learning environment and engaging teaching materials, which significantly contributed to student motivation. Overall, the level of student motivation in learning English during the Covid-19 pandemic at SMPN 27 Makassar, reaching  72.23,  falls  within  the  category  of  very  high  motivation.  The  Intrinsic factors instance perseverance in following English learning, feeling of necessity in English language learning, and the expectations and aspirations associated with English language learning play a crucial role in student intrinsic motivation. Additionally, the extrinsic factors instance a supportive learning environment, engaging teaching methods, and the availability of adequate learning facilities, significantly contribute to students' motivation.Keywords: Motivation, Motivational Factor, English Learning